The Comparison of DGA Interpretation Techniques Application for Actual Failure Transformer Inspections Including Experience from Power Plants in Thailand - Korraya Jongvilaikasem; Norasage Pattanadech; Wilasinee Wattakapaiboon; Masaaki Kando; Sakda Maneerot; Pittaya Pannil (International Journal on Electrical Engineering and Informatics, 2022)
Dissolve gas analysis (DGA) is a diagnostic test technique applied for transformer condition evaluation. The interpretation of the dissolved gas results is a significant procedure to classify the incipient fault types in transformers. A variety of dissolved gas interpretation methods utilized for the same investigation case may give different fault type results. This paper investigates the performance of dissolved gas interpretation methods, including Doernenburg Ratio, Roger Ratio, IEC Ratio, Mller-Schlliesing and Soldner Method, Duval Triangle, and Duval Pentagon. The twenty-four failure transformer cases are used to evaluate the performance of the dissolved gas interpretation methods. The test result shows that the Duval pentagon interpretation technique shows the highest consistency interpretation. Besides, the Duval pentagon method demonstrates the ability to identify a normal aging problem of the transformer insulation.
Keywords: Non-Destructive Testing Techniques; Concrete Corrosion and Durability; High voltage insulation and dielectric phenomena